Design of Short Circuit Indicator for Medium Voltage Systems - Adil Alahmad (Indonesian Scientific Journal, 2023)
A phenomenon known as a short circuit occurs when the input terminals of a power source come into direct electrical contact with one another, which results in a very high flow of current. This results in the production of a significant amount of heat, which poses a risk to the system itself and those located nearby. So, it is vital to identify a short circuit problem and rapidly respond to it once it is identified. When connected, the Short Circuit Indicator automatically detects a short circuit in a circuit to which it is attached. We were able to show the short circuit in our circuit board by inserting a piece of wire that has a resistance value that is very low, almost equal to zero, and which, as a result, created a short circuit at the source connection. Three single-phase currents imply high voltage power line short faults. Zero sequence currents imply grounding failure. Line patrollers may see or hear short circuits or grounding issues on 3kV-40.5kV power distribution networks, switchgear, cable branching units, etc. Answer